Hospitality and artistic activism in and around 2001 - Di Paola, Modesta (Escritura e Imagen, 2024)
The relationship that activist art weaves with society is very often nourished by the moods of society itself, transforming public actions in collective complaints and generational quarrels that record the different human reactions to current historical events. An emblematic case that explains this relationship is found in the 9/11 attacks on the Twin Towers in New York, which in 2001 generated the so-called fight against international terrorism, whose aims hid a radical anti-immigration policy, and hid in several countries the suspension of some constitutional rights. In light of this event, we witnessed the intensification of nationalist discourses, the generation of a feeling of fear towards the foreigner and the consequent political measures that until today neither concealed nor qualified the xenophobic component that the beginning of the 21st century suffers. However, from the artistic field it generated an emblematic reaction that if on the one hand it acted as a social seismograph measuring social moods, on the other hand it promoted a political activism that spread internationally. Many activist artists and performers have given a fundamental contribution with extraordinary artistic examples that have recognized the feeling of hospitality as the key against all xenophobic discourse, and have used it as a conceptual basis to explain the dynamics of coexistence between individuals and societies.
Keywords: hospitality; ethics; xenophobia; perfomance; political activism; 2001